Etnofarmakologi dan Inventarisasi Tumbuhan Obat di Kecamatan Kapuas Hilir Kabupaten Kapuas Kalimantan Tengah - Nurul Qamariah; Rezqi Handayani; Opi Indriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Ethnopharmacology is the study of the use of plants that have pharmacological effects for the treatment and health care of an ethnic group. The ethnopharmacological study was conducted in Kapuas Hilir District, Kapuas Regency. This is because the people of Kapuas Hilir District, Kapuas Regency still use medicinal plants to cure diseases whose properties have been known from generation to generation. This study aims to obtain data in the form of plant species, parts used, processing methods and to find out whether the empirical properties of the medicinal plants used are supported by research data. This research was conducted using qualitative research methods with descriptive design, techniques in data collection using observation, interviews, and documentation. The results showed 22 types of medicinal plants used to treat various diseases, namely Rabangun, Cat's Whiskers, Keji Beling, Sawangkak, Karamunting Bulu, Kastela, Soursop, Mangkudu, Katatuak, Gusar, Kalanduyung, Tabuluh, Insulin, Galinggang, Urang Iru, Uru. Balanda, Henda Baputi, Uru Samue, Panawar Gantung, Breadfruit, Pahakung, and Kalamenyu. The plant parts used are the bark, rhizomes, flowers, herbs, stems, roots and the most widely used are the leaves. The processing method is soaked in warm water, burned, made capsules, consumed directly, pounded, and processed by boiling most often. Most of the empirical properties of medicinal plants used are still not supported by research data.